DEPICTION OF VIRULENT IN RACISM AND AN UNDEFINED FUTURE OF AFRICANS IN ERNEST J. GAINES’S CATHERINE CARMIER - Jayakumar, J.; Thire Karan Rajan, S.A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Being a one of the most illustrious African American novelists Ernest J. Gaines has written numerous novels to his contribution. He meticulously focused the sufferings of Africans by the white domination. The prime objectives of his novels are Racism, Gender issue, Socio-Economic status of Africans, Alienation and Isolation. In the series of Chinua Achebe, Ngugi Wa’ Thiong’O and Flora Nwapa Ernest J. Gaines also been considered as one among the most resourceful and inspirational novelist. Gaines was born on a Louisiana plantation in 1933 in the midst of the Great Depression. He began working the fields when he was nine, digging potatoes for fifty cents a day. He spent most of his childhood with his aunt, Augustan Jefferson, a determined woman who had no legs but managed to take care of her family. Gaines considered her the most courageous person he ever knew. At age fifteen, Gaines moved to Vallejo, California, joining his parents who had moved there during World War II. In Vallejo, Gaines discovered the public library. Since he could not find many books written about the experience of African Americans, he decided to write his own. In 1964 Gaines has published his first novel, Catherine Carmier and after he published the novel Of Love and Dust three years, followed by a short story collection entitled Bloodline (1968) and another entitled A Long Day in November (1971). He received little attention for these efforts, but felt happy about his progress as a writer. In 1971 Gaines completed one of his most famous novels, The Autobiography of Miss Jane Pittman. The novel follows the life of a fictional woman, Jane Pittman, who is born a slave and lives to see the Black Power movement of the 1960s. After the critical and financial success of The Autobiography of Miss Jane Pittman, Gaines published several more novels on the topic closest to his own heart: the black communities of Louisiana. The most successful of these was A Lesson Before Dying, which was nominated for the Pulitzer Prize and, in 1993, won the National Book Critics Circle Award. Catherine Carmier, however, is much more than a love story, as its critics have recognized. Their descriptions focus on relationships within the families of the plantation quarters; caste conflicts, past and present, within the Louisiana black community facing changes in old social and racial codes; the psychology of racial prejudice and racial identity; and the struggle for human relationships in this context. The novel expands on all these issues. Taken as a whole, however, it is a story of the struggle for human maturation through choices-choices young people must make when early loves conflict with new loves, when commitments to family, race, culture, and religion collide with the need to move independently beyond the limits of those communities. As in the short stories, individual movement away from the quarters community is expected and reluctantly supported for young men; commitment to home folks and values is expected, and virtually required, of young women. The novel takes the boys of the stories into young adulthood, when manhood is still to be defined. It enlarges on "Mary Louise" by reintroducing the choices facing young women. It is a story of the question of whether, in their circumstances, young people can choose at all-freely choose any love at all.